Implementation of Artificial Intelligence (AI) in Human Resource Management: A Literature Review - Muhammad Joko Susilo; Denies Priantinah (International Journal Business, Management and Innovation Review, 2025)
This research aims to examine in depth the impact of Artificial Intelligence (AI) implementation on the human resource management process. This research was conducted through a literature review by collecting information from reputable journal articles, through descriptive research methods and qualitative approaches. Data was collected through snowball observation technique with the criteria of Scopus indexed journal articles Q1-Q4 within the last 5 years. Data analysis was conducted through data presentation, data reduction and conclusion. The findings of this study provide deep insight into the complexity of the relationship between Artificial Intelligence and human resource management, AI plays an important role in the human resource management process starting from recruitment, selection, employee training and development, performance appraisal, decision making, determining employee compensation and benefits as well as relationships with customers.